Synthesis, enzyme inhibition, and docking studies of new schiff bases of disalicylic acid methylene-based derivatives as dual-target antibacterial agents - Al-Wahaibi, Lamya H.; Mahmoud, Mohamed A.; Alzahrani, Hayat Ali; Abou-Zied, Hesham A.; Abdelmoez, Alshaimaa; Youssif, Bahaa G. M.; Bräse, Stefan; Rabea, Safwat M. (Frontiers in Chemistry, 2024)
Bacteria have acquired resistance to almost all antibiotics currently in use due to their extensive, broad, and improper utilization over a prolonged period. DNA gyrase and DHFR exhibit significant promise as targets for antibacterial therapeutics. We have developed a series of disalicylic acid methylene/Schiff bases hybrids (6a-l) that function as antibacterial agents by targeting DNA gyrase and DHFR. The findings showed that 6a-l have significant antibacterial activity against both Gram-positive and Gram-negative bacteria, with inhibition zones (IZ) comparable to or even higher than the reference Ciprofloxacin. MIC testing revealed that 6h and 6l were 1.5 times as effective than ciprofloxacin against S. aureus. Compounds 6h and 6l had MBC values of 28 and 33 nM for S. aureus, compared to Ciprofloxacin's 45 nM, indicating that they are more potent bactericidal agents. The MIC values for compounds 6c, 6e, 6h, 6j, and 6l against A. flavus were between 14.50 and 19.50 µM, while the MIC value for fluconazole was 11.50 µM. Also, the studied compounds had MIC values between 18.20 and 22.90 µM against C. albicans, while Fluconazole had a MIC value of 17.50 µM. Compound 6h showed a MIC value of 1.70 µM against the clinical strain S. aureus (ATCC 43300) (MRSA), making it an effective antibacterial agent. Compounds 6h, 6j, and 6l inhibited E. coli DNA gyrase with IC50 values of 79, 117, and 87 nM, respectively, compared to the reference novobiocin (IC50 = 170 nM). Additionally, compounds 6h and 6l, the most potent E. coli gyrase inhibitors, showed encouraging results on DHFR.Compounds 6h and 6l exhibit IC50 values of 3.80 µM and 4.25 µM, respectively. These values are significantly lower and hence more effective than Trimethoprim's IC50 of 5.20 µM.